Film Tourism in Basilicata - Bencivenga, Angelo; Chiarullo, Livio; Colangelo, Delio (Almatourism - Journal of Tourism, Culture and Territorial Development, 2015)
Film tourism is the phenomenon that is born from the desire to visit film locations, drawing increasing attention in recent years. This paper presents the results of a field research aiming at analysing the effects of the film Basilicata coast to coast, by Rocco Papaleo, on tourism in Basilicata, a small region in the South of Italy, after the film’s success at the box office, winning several Italian awards. The film, made with the active involvement of local institutions and stakeholders, pursues the objective of promoting an area that is still largely unknown to national and international tourists. The romantic and naturalistic atmosphere of Papaleo's film seems to have stimulated the curiosity of tourists and promoted a "dream-like" but truthful image of the region.